Penerapan Model Sains Teknologi Masyarakat (STM) Berbasis Produk Pada Materi Fungi Untuk Meningkatkan Pemahaman Konsep Siswa - Rahmat Hidayatullah; Nisa Sholehah Pangsuma; Meti Maspupah; Sri Maryanti (Jurnal Bintang Pendidikan Indonesia, 2023)
Understanding the concept plays a very important role in learning, so that it becomes the basis for achieving learning outcomes. Choosing the right learning model can affect students' understanding of a concept. The product-based Science Technology Society (STS) learning model is likely to improve students' conceptual understanding. This study is a qualitative study with a pre-experimental method and a pre- and post-test using a single-group design. An observation point and a test device were used as research tools. The results showed that students' understanding of the concepts improved significantly with the implementation of the product-based Science Technology Society (STS) model. This is taken into account by the T-test results where the t-table results are less than the t-number. Therefore, it can be concluded that the use of product-based models of science technology and society (STS) significantly affects students' understanding of concepts.